Calcineurin B stimulates cytokine production through a CD14‐independent Toll‐like receptor 4 pathway. Issue 3 (17th November 2015) - Wu, Wu; Chen, Qing; Geng, Feng; Tong, Li; Yang, Rui; Yang, Jinju; Zhang, Hongwei; Jia, Zongchao; Wei, Qun
Abstract : The calcineurin B subunit (CnB) is the regulatory subunit of Cn, a Ca 2+ /calmodulin‐dependent serine/threonine protein phosphatase. In this study, we demonstrate that extracellular CnB was effectively internalized through a CD14‐independent Toll‐like receptor 4 (TLR4) pathway, which led to the phosphorylation of nuclear factor (NF)‐kappa‐B inhibitor alpha (IκB‐α) and upregulation of pro‐inflammatory cytokines in human monocytes. CnB‐induced IκB‐α phosphorylation is completely dependent on TNF receptor‐associated factor 3 (TRAF3) but not TRAF6, which is indispensable for IκB‐α phosphorylation in response to lipopolysaccharide. The loss‐of‐function CnB mutants were able to induce IκB‐α phosphorylation, further indicating that this novel role of CnB is completely independent of the phosphatase function of Cn. Taken together, these findings demonstrate that CnB is a novel host‐derived immunostimulatory factor, having a role as an agonist in monocytes, and specificity in TLR4 signaling through TRAF3 and TRAF6, in response to various agonists.